2017
DOI: 10.3390/en10030302
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Transpired Solar Air Collectors and Metal Corrugated Packing Solar Air Collectors

Abstract: Abstract:The thermal performance of three novel solar air collectors with perforating corrugated plate, slit-perforated plate, and corrugated packing were experimentally studied in this paper. Experiments were conducted in Tianjin to study the thermal and dynamic performance of the collectors in cold and severe cold regions. A chamber with a PID (Proportion Integration Differentiation) temperature controller was designed to control the inlet air temperature of the three collectors. Effects of radiation intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…While numerous authors reported favorable results [24] after improving the efficiency of the transpired collectors, some experimentally and numerically studied the unglazed transpired collector in cold claimant for heating space [25]. Moreover, some researchers used transpired solar collectors with perforating corrugated plates [26], or protruded absorber plates with roughened solar air heaters [14], and others were invented, such as the absorber plate with circular holes, slit-like perforations, multi v-shaped gap ribs, and roughened protrusions [27], enabling them to save a large amount of thermal energy.…”
Section: Introductionmentioning
confidence: 99%
“…While numerous authors reported favorable results [24] after improving the efficiency of the transpired collectors, some experimentally and numerically studied the unglazed transpired collector in cold claimant for heating space [25]. Moreover, some researchers used transpired solar collectors with perforating corrugated plates [26], or protruded absorber plates with roughened solar air heaters [14], and others were invented, such as the absorber plate with circular holes, slit-like perforations, multi v-shaped gap ribs, and roughened protrusions [27], enabling them to save a large amount of thermal energy.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional solar air heaters consist of an absorber plate and a glass cover on top of it that forms a narrow channel wherein the air stream is heated in and directed through it [6]. Since different factors, such as mass flow rate, plate sheet material, cover type, collector dimensions, etc., affect the solar air heater performance, researchers have adopted different techniques to increase the performance of solar collectors by changing the configuration of the system [7][8][9]. However, the optimization of the thermal performance of solar air heaters is still a major challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Solar air collectors are simple devices, however have a numerous of options of constructive execution, warming, a material and a covering of an absorber, a translucent covering, and means of ensuring creation of turbulent air streams inside. Therefore, a large number of scientific studies of various authors is devoted to the study of their properties and design features [8][9][10][11][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%